Teaching MDE through the Formal Verification of Process Models - Combemale, Benoit; Cregut, Xavier; Dieumegard, Arnaud; Pantel, Marc; Zalila, Faiez (Electronic Communications of the EASST, 2012)
Model Driven Engineering (MDE) and formal methods (FM) play a key role in the development of Safety Critical Systems (SCS). They promote user ori- ented abstraction and formal specification using Domain Specific Modeling Lan- guages (DSML), early Validation and formal Verification (V&V) using efficient dedicated technologies and Automatic Code and Documentation Generation. Their combined use allow to improve system qualities and reduce development costs. However, in most computer science curriculae, both domains are usually taught independently. MDE is associated to practical software engineering and FM to the- oretical computer science. This contribution relates a course about MDE for SCS development that bridges the gap between these domains. It describes the content of the course and provides the lessons learned from its teaching. It focuses on early formal verification using model checking of a DSML for development process mod- eling. MDE technologies are illustrated both on language engineering for CASE tool development and on development process modeling. The case study also highlights the unification power of MDE as it does not target traditional executable software.